Zadanie 1.
z podanego wzoru wyznacz niewiadomą y. Załóż, że wszystkie niewiadome są liczbami dodatnimi

a) 2y - ab = c
b) b = -ay + dv
c) ay - c = 4ay - d
d) 3by - z - a = 2by

Zadanie 2.
z podanego wzoru wyznacz niewiadomą z. Załóż, że wszystkie niewiadome są liczbami dodatnimi

a) z/a = t/c
b) b/z = 4x/d
c) x = a+b/z
d) z²a = c
e) z/a = b/z
f) z² + 1/c = b/3

3

Odpowiedzi

2010-03-23T16:58:17+01:00
Zad.2
a)zc=at/:c
z=at/c
b)4xz=bd/:4x
z=bd/4x
2 3 2
2010-03-23T17:05:01+01:00
A) 2y - ab = c
2y=c+ab
y=c+ab/2

b) b = -ay + dv
b-dv=-ay
-b+dv=y

c) ay - c = 4ay - d
ay-4ay=-d+c
-3ay==-d+c
y=-d+c/-3a

d) 3by - z - a = 2by
3by-2by=z+a
by=z+a
y=z+a/b

2.
a) z/a = t/c
zc=at
z=at/c

b) b/z = 4x/d
bd=4xz
bd/4x=z

c) x = a+b/z
xz=a+b
z=a+b/x

d) z²a = c
z²=c/a
z=(pierwiastek)c/a

e) z/a = b/z
z²=ab
z=(pierwiastek)ab

f) z² + 1/c = b/3
z² =b/3-1/c
z² =bc/3c-3/3c
z² =bc-3/3c
z² =(pierwiastek)bc-3/3c


4 4 4
Najlepsza Odpowiedź!
2010-03-23T17:17:21+01:00
A)2y-ab=c
2y=c+ab
y=(c+ab) /2

b) b-ay+dv
b-dv=ay/:(-a)
(b-dv)/(-a) = y

c)
ay - c = 4ay-d
ay- 4ay = -d+c
y= (-d+c)/(3a)

d)
3by - z- a =2by

3by - 2by = z+a
by= z+a
y= (z+a)/(b)


zadanie 2
a)
z/a = t/c
zc=at
z= (at)/c
b)
b/z=4x/d
4zx=bd
z= (bd)/4x
c)
x =(a+b)/z
z= (a+b)/x

d)
z²a=c
z=√(c/a)

e)

z/a=b/z
z²=ab
z=√(ab)

f)

z²+1/c = b/3
z²= (b/3)-(1/c)
z=√((b/3)-(1/c))

4 5 4